The unexplored crossroads of the female athlete triad and iron deficiency: A narrative review - Petkus, D. L.; Murray-Kolb, L. E.; De Souza, M. J. (Sports Medicine, 2017)
Despite the severity and prevalence of iron deficiency in exercising women, few published reports have explored how iron deficiency interacts with another prevalent and severe condition in exercising women: the `female athlete triad.` This review aims to describe how iron deficiency may interact with each component of the female athlete triad, that is, energy status, reproductive function, and bone health. The effects of iron deficiency on energy status are discussed in regards to thyroid function, metabolic fuel availability, eating behaviors, and energy expenditure. The interactions between iron deficiency and reproductive function are explored by discussing the potentially impaired fertility and hyperprolactinemia due to iron deficiency and the alterations in iron metabolism due to menstrual blood loss and estrogen exposure. The interaction of iron deficiency with bone health may occur via dysregulation of the growth hormone/insulin-like growth factor-1 axis, hypoxia, and hypothyroidism. Based on these discussions, several future directions for research are presented.